The effects of wage subsidies for older workers - Bernhard Boockmann (IZA World of Labor, 2015)
Population aging in many developed countries has motivated some governments to provide wage subsidies to employers for hiring or retaining older workers. The subsidies are intended to compensate for the gap between the pay and productivity of older workers, which may discourage their hiring. A number of empirical studies have investigated how wage subsidies influence employers' hiring and employment decisions and whether the subsidies are likely to be efficient. To which groups subsidies should be targeted and how the wage subsidy programs interact with incentives for early retirement are open questions.
Keywords: J64; H24; C31; 330; long-term unemployment; active labor market programs; older workers; early retirement; labor demand; wage subsidies